2021
DOI: 10.3389/fmicb.2021.742931
|View full text |Cite
|
Sign up to set email alerts
|

Single and Repeated Episodes of Candida Species Isolated From Cerebrospinal Fluid for Diagnosing Probable Candida meningitis

Abstract: Background: The clinical relevance of single or repeated episodes of Candida spp. in cerebrospinal fluid (CSF) in adult patients is debatable.Methods: Forty-two patients with positive Candida episodes in CSF were enrolled in this retrospective study.Results: A total of 42.9% (18/42) were determined to have probable Candida meningitis (PCM). Neurosurgery [odds ratio (OR) (95% confidence interval), OR: 14.4 (1.6–126.1), P = 0.004], lumbar drainage [OR: 5.8 (1.5–23.3), P = 0.009], VP shunt [(OR: 5.6 (1.2–25.8), P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…that six of the 23 patients with CM in the neonate period were expired (11). Lijun Xu et al reported 50% mortality in their CM cases (12). In a study conducted on patients other than neonates, 42% of CM-related deaths were reported (21).…”
Section: Discussionmentioning
confidence: 97%
“…that six of the 23 patients with CM in the neonate period were expired (11). Lijun Xu et al reported 50% mortality in their CM cases (12). In a study conducted on patients other than neonates, 42% of CM-related deaths were reported (21).…”
Section: Discussionmentioning
confidence: 97%